Factors associated with the use of over-the-counter sleep aids containing diphenhydramine: A cross-sectional study in Saudi Arabia - Khalid Alhussain; Dimah I. Almuayli; Sara M. Aldaej (Elsevier, 2023)
Introduction: Diphenhydramine, either alone or in combination with pain relievers, is one of the widely used over-the-counter sleep aids. However, few studies have evaluated the use of diphenhydramine-containing products, such as Panadol Night, in Saudi Arabia. Therefore, the objectives of this study were to assess the prevalence of Panadol Night use and to identify factors associated with its use in the Eastern Province of Saudi Arabia. Methods: A cross-sectional study was conducted among adults aged 18 years or older in the Eastern Province of Saudi Arabia. Data were collected through an online self-administered questionnaire from 05 March 2022 to 20 March 2022. Chi-square tests and multivariable logistic regression models were used to examine the associations between Panadol Night use in the past month and independent variables. Results: A total of 1244 adults participated in the survey. Approximately, 42.3% reported that they have used Panadol Night in their lifetime; 12.1% used Panadol Night in the past month. The majority of the Panadol Night users (62.4%) reported that their use was based on their family/friends' recommendations, while 23.6% used Panadol Night based on healthcare providers' recommendations. The multivariable logistic regression models showed that gender, health related fields, perceived safety and effectiveness of Panadol Night, a history of insomnia, trouble sleeping due to pain, and sleep quality were significantly associated with the use of Panadol Night in the past month. Conclusions: Our findings indicated that adults' perceptions of the effectiveness and safety of Panadol Night were significantly associated with its use. Also, adults in non-health related fields were more likely to use Panadol Night compared to those in health related fields. This suggests the need for raising awareness about the appropriate use of Panadol Night. Community pharmacists can play an essential role in educating patients during the time of purchase.